Role of the hydrolytic‐acidogenic phase on the removal of bisphenol A and sildenafl during anaerobic treatment (2023)
ABSTRACT: This paper presents the main results of the removal of two pharmaceutical and personal care products (PPCPs), bisphenol A (BPA) and sildenafl (SDF), by applying anaerobic biological batch tests. The biomass used was previously acclimatized and the experiment lasted 28 days. The efect of factors such as compound (BPA and SDF), concentration and type of inoculum was assessed, considering the factorial experimental design. The results indicated that evaluated factors did not signifcantly afect the PPCPs elimination in the evaluated range with a confIdence level of 95%. On the other hand, the removal percentages obtained with BPA were mainly related to mechanisms, such as sorption and abiotic reactions. Regarding SDF, biodegradation was the predominant mechanism of removal under the experimental conditions of this study; however, the degradation of SDF was partial, with percentages lower than 43% in the tests with hydrolytic/acidogenic inoculum (H/A) and lower than 41% in the tests with methanogenic inoculum (MET). Finally, these fndings indicated that hydrolysis/acidogenesis phase is a main contributor to SDF biodegradation in anaerobic digestion. The study provides a starting point for future research that seeks to improve treatment systems to optimize the removal of pollutants from diferent water sources.